Relationship between labor force participation and unemployment in Pakistan - Said, Rusmawati; Amjad, Sadaf; Khan, Muhammad Zaheer (Economics Bulletin, 2024)
This paper investigates the relationship between labor force participation and unemployment in Pakistan using the annual time series data for the period 1990-2021. Johansen's cointegration and Gregory and Hansen's cointegration tests determine the long-run relationship between unemployment and labor force participation rate for aggregate male and female workers. Both cointegration procedures confirm no long-run relationship between the variables. Therefore, the results confirm the unemployment invariance hypothesis for aggregate and male and female workers in Pakistan.